The identity of Hedychium marginatum C.B. Clarke (Zingiberaceae), and a new species, H. Nagamiense from North-eastern India (Bangladesh Journal of Plant Taxonomy, 2011)
The identity of Hedychium marginatum C.B. Clarke is corrected based on the type and protologue studies and H. luteum Baker is reduced as its synonym. H. nagamiense Sanoj et al. sp. nov., from Nagaland, India is described and illustrated. Nomenclatural notes, phenology, geographical distribution and IUCN status of both species are provided.Keywords: Hedychium luteum; H. marginatum; H. nagamiense; New species; New synonym; Taxonomic identity; Zingiberaceae.DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9304Bangladesh J. Plant Taxon. 18(2): 169-176, 2011 (December)